Seroprevalensi Avian influenza H5N1 pada Unggas di Kabupaten Aceh Utara - Darmawi Darmawi; Darniati Darniati; Maryulia Dewi; Fakhrurrazi Fakhrurrazi; Mahdi Abrar; Erina Erina (Agricultural Faculty, 2013)
Seroprevalence of avian influenza H5N1 in birds in north aceh districtABSTRACT. Avian influenza virus H5N1 infections are an important cause of diseases in humans and several animal species, including birds. The present study conducted to investigate the seroprevalence Avian Influenza H5N1 in native birds from 15 sub-districts of North Aceh. This study utilized 1108 serum samples collected from the axilaris vein (left or right) of birds. The standard Hemaglutination Inhibition (HI) assay was conducted at Microbiology Laboratory Faculty of Veterinary Medicine of Syiah Kuala University to determined serum antibody possitive or negative reaction against Avian influenza H5N1. The result showed that seroprevalence Avian influenza H5N1 virus was 4,7 % in North Aceh District. There were nine sub-districts were tested positively by HI test. However, the serum collected from six sub-districts did not react (negative) against Avian influenza H5N1. Based on the results we obtained, a conclusion that natural infection by Avian influenza virus in native birds occured in part of North Aceh District.